2019
DOI: 10.1111/ejh.13317
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab added to standard of care in patients with newly diagnosed multiple myeloma: A network meta‐analysis

Abstract: Purpose: To investigate the activity and safety of daratumumab added to standard of care and evaluate the relative efficacy of DRd vs DVMP and other regimens on survival endpoints for untreated myeloma, we undertook this meta-analysis. Methods:We searched published reports that described the activity and safety of daratumumab added to standard of care for untreated myeloma. Results: Six daratumumab trials were identified, covering 5106 subjects. Daratumumab containing combinations for untreated myeloma attaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…A We found that both daratumumab-containing regimens evaluated (D-Rd and D-VMP) and VRd consistently had better PFS than Rd continuous; this finding was also seen in the simplified network of comparators relevant for Europe despite the different SOC options. These results are consistent with those of previous NMAs, including Cao et al [9], Ramasamy et al [13], and Xu et al [12] (D-Rd versus Rd PFS HRs, 0.57, 0.57, and 0.55, respectively). Cao et al also observed an advantage for D-VMP versus Rd (PFS HR, 0.59) [9], whereas the other studies were favourable but with different point estimators (PFS HRs, 0.73 and 0.71, respectively) [12,13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A We found that both daratumumab-containing regimens evaluated (D-Rd and D-VMP) and VRd consistently had better PFS than Rd continuous; this finding was also seen in the simplified network of comparators relevant for Europe despite the different SOC options. These results are consistent with those of previous NMAs, including Cao et al [9], Ramasamy et al [13], and Xu et al [12] (D-Rd versus Rd PFS HRs, 0.57, 0.57, and 0.55, respectively). Cao et al also observed an advantage for D-VMP versus Rd (PFS HR, 0.59) [9], whereas the other studies were favourable but with different point estimators (PFS HRs, 0.73 and 0.71, respectively) [12,13].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of previous NMAs, including Cao et al [9], Ramasamy et al [13], and Xu et al [12] (D-Rd versus Rd PFS HRs, 0.57, 0.57, and 0.55, respectively). Cao et al also observed an advantage for D-VMP versus Rd (PFS HR, 0.59) [9], whereas the other studies were favourable but with different point estimators (PFS HRs, 0.73 and 0.71, respectively) [12,13]. This divergence in benefit is potentially attributable to the different data cut-offs for ALCYONE and VISTA used in the analyses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mechanism of action of daratumumab is based on the elimination of tumor cells expressing high levels of CD38 through antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity. Recent studies have reported an increased risk of infection in multiple myeloma patients undergoing treatment with daratumumab, either as monotherapy or as combined therapy with other drugs, with some cases resulting in lethal sepsis [87][88][89][90][91][92][93]. Infections reported as drug-related adverse effects include opportunistic bacterial infections of the respiratory or urinary tracts (e.g., S. pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli and Haemophilus influenzae), exogenous viral infections (e.g., acute respiratory syncytial virus, human metapneumovirus and influenza A and B viruses) and viral reactivations (e.g., cytomegalovirus, herpes simplex virus and varicella-zoster virus).…”
Section: Increased Risk Of Infections In Immunotherapies Using Anti-cmentioning
confidence: 99%
“…Xu et al found that addition of daratumumab to first-line regimens (bortezomib, melphalan, and prednisone or lenalidomide and dexamethasone) significantly improves PFS, compared to the same regimens alone, in NDMM. Furthermore, in their study, patients receiving daratumumab, compared to patients on the control arms, had a higher chance to achieve complete response (CR) rate or better 7 . Similar benefit of daratumumab was found by Wang et al regarding CR or better in relapsed/refractory MM (RRMM) 8 .…”
Section: Introductionmentioning
confidence: 99%